(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
In the article the space-time, functional structures and mutual relations between day and week cycles of peoples’ life activities have been analyzed. Some space-time rules and features of peoples’ life activities functioning depending on size functional type and economic-geographical position of the communities in Armenia have been revealed.